1994
DOI: 10.1073/pnas.91.22.10370
|View full text |Cite
|
Sign up to set email alerts
|

Conformational isomerism and the diversity of antibodies.

Abstract: The fact that one cell encodes a single antibody sequence does not ne arily mean that the resulting antibody folds into a single structure, although this is a common assumpton. Here we challenge this view and suggest that many antibodies do not have a single conformation at the combining site.The basis for this proposal comes from the kinetic analysis of a set of murine hybridomas derived from defined stages of the immune response to 2-phenyl-5-oxazolone (Ox). Among them we have identified three antibodies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
216
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(233 citation statements)
references
References 24 publications
16
216
0
1
Order By: Relevance
“…However, recent crystallographic and thermodynamic analyses of both germline and mature Ab-Ag complexes have suggested that the Ab repertoire can be further enhanced at the tertiary structural level (7,14,18,19,34,35). The present study provides an elegant correlation of CDR conformational versatility in a germline Ab with its multispecificity.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, recent crystallographic and thermodynamic analyses of both germline and mature Ab-Ag complexes have suggested that the Ab repertoire can be further enhanced at the tertiary structural level (7,14,18,19,34,35). The present study provides an elegant correlation of CDR conformational versatility in a germline Ab with its multispecificity.…”
Section: Discussionmentioning
confidence: 70%
“…Our data illustrate the importance of paratope adaptability *Structural Biology Unit, National Institute of Immunology, New Delhi 110 067, India; and † Regional Centre for Biotechnology, Gurgaon 122 016, India for facilitating polyreactivity of germline mAb through systematically designed crystallographic experiments. The present analysis, in light of earlier studies (1,5,8,9,(14)(15)(16)(17)(18)(19), suggests the possibility that generation of diversity in the primary Ab repertoire may involve multiple mechanisms in a hierarchical order. The proposed model may account for enhanced diversity of primary immune receptors without increasing the size of the germline gene repertoire.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, these states/substates can interconvert, with the transition rate determining the probability distribution and population size of these states. Based on the thermodynamic and kinetic properties of proteins, a more "real" model, the conformational selection model [87][88][89] was proposed to explain the protein-ligand binding mechanism at the molecular population level.…”
Section: Conformational Selection Mechanism Of Protein-ligand Bindingmentioning
confidence: 99%
“…This loss in flexibility is due to an increased effective correlation time (in this case, probable loss of flexibility of the binding site for hapten), leading to a larger negative NOE (that is, the cross-peaks are in the same phase as the diagonal peaks and have an increased intensity). Conformational mobility of the antibody combining site has been proposed as a possible mechanism for cross-reactivity and multiphasic binding kinetics (Foote & Milstein, 1994). Such a mechanism may be common.…”
Section: Discussionmentioning
confidence: 99%